Fast food and sweet intake pattern is directly associated with the prevalence of asthma in a Qatari population - Zumin Shi (287671) (2022)
Objective The relationship between dietary patterns and the prevalence of asthma is not well understood. We aimed to investigate the association between dietary patterns and asthma in adults in Qatar. Methods In this study, cross-sectional data from the Qatar Biobank were used (n = 986). Participants were Qatari or long-term Qatar residents aged ≥20 years old. A food frequency questionnaire was used to collect dietary intakes. Three dietary patterns were identified using factor analysis. Multivariable logistic regression was used to assess the association between dietary patterns scores and asthma. Results Among 986 eligible participants, 6.6% (n = 65) reported that they were diagnosed with asthma. Three dietary patterns were identified. These were (1) “Traditional” (high intake of rice, chicken/meat/fish, and breads); (2) “Prudent” (high intake of fruits, vegetables, and fish); and (3) “Fast Food/Sweets” (high intake of desserts, fast food, and soft drinks). The fast food/sweet dietary pattern was associated with increased likelihood of having asthma [comparing high vs. low tertile, OR for asthma = 1.25; 95% CI (1.02–1.54); p = 0.035]. Traditional and Prudent dietary patterns were not associated with the prevalence of asthma. Conclusion The fast food/sweet dietary pattern was directly associated with the prevalence of asthma among adults in Qatar. Reducing the fast foods and sugary-rich foods may be beneficial for respiratory health. Other Information Published in: European Journal of Clinical Nutrition License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41430-021-00959-6